Leader Characteristics and Constitutional Compliance - Jerg Gutmann; Katarzyna Metelska-Szaniawska; Stefan Voigt (University of Hamburg, Institute of Law and Economics (ILE), 2023)
While research in constitutional economics has made important progress in recent decades, the factors determining whether a constitution is complied with have only received scant attention. We contribute to that narrow literature by studying how personal traits of political leaders are associated with constitutional compliance. Compliance levels of 943 political leaders between 1950 and 2010 can be explained by their education, entry into office, political experience, military background, and whether they are members of extreme left-wing parties. Specifically, under former military officers and Communist leaders, constitutional compliance is significantly lower. The combined effect of these two traits corresponds to the difference between democracy and nondemocracy. This implies a difficult normative question, which we discuss in our conclusion: Should constitutions set entry barriers for high political offices that are based on leader characteristics?
Keywords: K10; K38; K42; P16; P26; P48; Z10; 330; constitutional compliance; de jure-de facto gap; leader characteristics